Pengaruh Sinergi Peserta Didik, Tujuan Pendidikan, Dan Materi Pembelajaran Terhadap Kualitas Hasil Belajar Di Era Pendidikan Modern - Nariswari, Fenina Nathaniela; Riskia, Ayu; Ernaningtyas, Fina; Ani, Firda; Firdausi, Soraya; Mahardika, I Ketut; Yusmar, Firda Ketut; Astuti, Sri Rejeki Dwi (Peneliti.net, 2025)
This research aims to develop a learning system that improves the quality of learning outcomes through synergy between students, educational goals, and learning materials in the modern education era. This research uses a development approach by modifying the Dick & Carey model which is integrated with the ADDIE model and ARCS elements (Attention, Relevance, Confidence, Satisfaction). The development process includes stages of analysis, design, development, implementation and evaluation. The research results show that the resulting learning system is of high quality and relevant to current educational needs. This system includes learning tools such as modules, media, learning agendas, as well as collaborative learning strategies that support the development of 21st century skills, such as critical thinking, communication, collaboration and creativity. Expert testing shows that this system is effective in creating innovative and meaningful learning, while increasing student motivation and satisfaction. This system makes new contributions to education, in particular by integrating various learning elements holistically to improve learning outcomes. Apart from that, this system also provides practical guidance that can be applied by educators at various levels of education. Thus, this research can be a reference for the development of other learning systems to answer educational challenges in the modern era.